Montenegro : Technical Assistance Report-Report on External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2020)
The IMF's Statistics Department (STA) conducted a technical assistance mission to support the Central Bank of Montenegro (CBM) for the compilation of external sector statistics in Montenegro during January 20-31, 2020. The mission recommended that the CBM compile preliminary quarterly International Investment Position data and submit them to STA for review by the end of December 2020. The mission recommended that the CBM start recording the Economic Citizenship Program (ECP) according to the characteristics of the payments from the applicants by the end of March 2020. The ECP was just introduced in 2019 and details of the program were not made available during the mission. The mission advised that the payments from applicants for the ECP should be recorded in services, current or capital transfers, or direct or portfolio investment, according to the characteristics of the payments. The CBM plans to start recording data based on the information obtained from the international transaction reporting system (ITRS). The mission advised that the CBM approach the agency in charge of the ECP to collect precise information on the characteristics of the payments and cross-check the data from the ITRS.